From a Foreign Religion to a Religion of Foreigners the Challenge of Contemporary Immigration to the Catholic Church in Japan - Oliveira, Antonio Genivaldo Cordeiro de (2017)
The presence of foreigner workers in Japan has had a great impact on the local Catholic Church. I will point out to data, which shows that the number of foreign believers has overtaken the number of Japanese believers. As a transnational religious institution, cooperation between the churches, which came from different countries, and Japanese Catholic churches would be the expected way to attend to the pastoral care of those Catholics. However, several conflicts have blocked that solution. Tensions and conflicts arise from the distinct understanding of organization of the local church and different command centers (such as National Bishops Conferences and the charismatic movement administrations). The article focuses initially on the intra-religious tensions resulting from the transplantation of a Pastoral Nipo-BrasileiraPANIB and the charismatic communities from Brazil to Japan. Further, I will show how the Catholic Church in Japan has adopted multiculturalism as the center of its policies of action aiming to become a model within Japanese society. All cases here presented have failed to offer an appropriate answer to the challenge of contemporary immigration with the Catholic Church.
Keywords: Catholic Charismatic Renewal; Immigration; Japanese Catholicism; Multiculturalism; PANIB